ANALYTICAL CAPABILITY AND VALIDATION OF A METHOD FOR TOTAL PETROLEUM HYDROCARBON DETERMINATION IN SOIL USING GC-FID - ŞENILĂ, Marin; LEVEI, Erika; ŞENILĂ, Lăcrimioara; CADAR, Oana; ROMAN, Marius; MICLEAN, Mirela (Studia Universitatis Babeș-Bolyai Chemia, 2015)
The paper presents the analytical capability and validation of a method for quantitative determination of total petroleum hydrocarbons in soil by gas chromatography with flame ionization detector (GC-FID). In order to validate the method, the main figures of merit such as limit of detection and limit of quantification, working range, precision and recovery were studied and the measurement uncertainty was estimated based on the bottom-up approach according to the international guidelines of ISO/IEC 17025. Limit of detection, estimated from chromatograms measured for spiked blank at low level mass concentration, was 8.3 mg/kg, while limit of quantification was 25 mg/kg. Precision was studied in terms of repeatability and reproducibility for the concentration range of 25 – 1000 mg/kg. Standard deviation of repeatability (sr) was 6.3% (n=10 parallel samples), while standard deviation of reproducibility (sR) was 9.9 % (n=10 parallel samples). Recovery (%) estimated using a certified reference material (CRM), was 93 ± 7.0 %, while the estimated expanded relative uncertainty was 17.2 %. This paper offers all the steps necessary to validate the determination method for total petroleum hydrocarbons in soil applied according to the standard ISO 16703 and to evaluate the measurement uncertainty for this method. The obtained figures of merit fulfil the requirements of the standardized method and also of the Romanian legislation and demonstrate that the laboratory can properly apply the method in order to achieve accurate results. The paper represents a model for the method validation in analytical laboratories in order to check the fit for purpose of analytical methods.